ASSESSMENT OF CREATIVE ECONOMY PRODUCTS AS INTELLECTUAL PROPERTY THAT CAN BE USED AS COLLATERAL IN BANKING WITH LEGAL CERTAINTY - Amselnius Siregar; Sukarmi; Yuliati (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This research aims to analyze the existence of the regulation in Government Regulation Number 24 of 2022 concerning the implementing regulation of the Creative Economy Law regarding financing based on intellectual property (namely: creative economy products) in Article 12 Paragraph 5. The appraiser in the a quo norm has the duty regarding intellectual property (creative economy products) to obtain financing from banking financial institutions and non-bank financial institutions. With the existence of intellectual property, there are benefits for aspects of community life and the enhancement of national growth. However, the reality that the regulation has not yet functioned ideally results in the development of intellectual property (creative economy products) needing to be followed up. This research is supported by normative (doctrinal) legal research methods with 2 (two) approaches, namely the statutory approach and the conceptual approach, all of which are analyzed prescriptively and analytically. Based on the research results, it is concluded that in a country it is very necessary: first, Government Regulation Number 24 of 2022 concerning the Implementing Regulation of the Creative Economy Law in the provisions of Article 12 paragraph 5 within legal certainty, the assessment of economic products as authorized appraisers has not yet had a standard for intellectual property appraisal because intellectual property is an intangible object that has different values (changing/not fixed) over time. Therefore, there is a need for a new government regulation to complement the existing regulations. This is because intellectual property plays a very significant role in the country's economic income.